Pengembangan soft skill siswa dalam pembelajaran matematika - Hidayati, Wiwin Sri; Tristanti, Lia Budi; Hudayana, Nur Alawi (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2023)
The aim of the research is to describe the soft skill development of students in learning mathematics. This research was conducted at MTsN 9 Jombang in the even semester of the 2022/2023 school year. Prospective subjects are students of class IXC, totaling 29 students. Next, one subject is selected who has the highest soft skills score to be analyzed in depth and comprehensively. The main instrument is the researcher himself and the supporting instruments include problem solving test sheets, observation guides and interview guides. Data collection techniques using problem-solving tests about Prism, observation and in-depth interviews. The credibility of the data in this study uses source triangulation. The technical stages of data analysis include data reduction, data presentation, and the last step is conclusion. The results showed that the development of verbal mathematical communication soft skills was in the high category, and the development of non-verbal mathematical communication soft skills was in the high category. Development of creative soft skills in the medium category. Development of critical thinking soft skills in the high category. Development of soft skills to solve problems in the high category. Development of stress management soft skills in the high category. Soft skills collaboration in the high category. Time management soft skills in the high category.